Quantitative histology of the acidophils of pars distalis adenohypophysis of Gaddi sheep (Ovis aries) - A seasonal study - PARAMASIVAN, S; SHARMA, D N (The Indian Journal of Animal Sciences, 2014)
The acidophils of sheep pituitary were differentially stained for somatotrophs and mammotrophs. A third type of acidophil called somatomammotroph was also observed, arranged mostly in clusters in the central area oftbe parenchymal cords of the pars distalis adenohypophysis. Somatotrophs (STH-cells) were large round, oval and polygonal cells with orange cyloplasmie granules. The average population of these cells was 1494±66,35 cells/mm2 during winter, which increased gradually in summer (1941± 125.98 cells/mm2). The results pointed towards their higher activity during summer and monsoon season and reduced activity duriilg winter. The mammotrophs were oval, round or elongated cells with carminophilic granules, which were mildly PAS-reactive and aldehyde fuchsin negative. The number of mammotrophs started increasing from spring (3668±97.06 cells/mm2) and reached to the maximum number during summer (4371 ±96 22 cells/mm2). which corresponds to lactating season or summer stress season.